Particle physics - Bishop, Christopher (London : John Murray, 2002)
Particle physics is the study of matter and energy at its most fundamental level. Successive discoveries during the 20th-century have led to dramatic changes in our understanding of matter at the sub-atomic level and current theories continue to be refined. Using the development of these theories, this text describes the basic structure of matter and the fundamental interactions that govern the workings of the universe as they are currently understood. It covers all aspects of particle physics required for A Level Physics, and is endorsed by the Institute of Physics.
Includes bibliography and index.
Keywords: Particle physics